Crystalloid and Colloid Compositions and Their Impact - Rudloff, Elke; Hopper, Kate (Frontiers in Veterinary Science, 2021)
This manuscript will review crystalloid (hypo, iso, and hypertonic) and colloid (both synthetic and natural) fluids that are available for IV administration with a focus on their electrolyte, acid-base, colligative and rheological effects as they relate to each solution’s efficacy and safety. The goal is for the reader to better understand the differences between each fluid and fluid combination on plasma composition, key organ systems, and their implications when used therapeutically in animals with critical illness.